Perlindungan Hukum Terhadap Hak Kekayaan Desain Industri Yang DiTiru Dan Diedarkan Tanpa Izin - Lainsamputty, Marcia; Akyuwen, Rory Jeff; Narwadan, Theresia Nolda Agnes (Faculty of Law Universitas Pattimura, 2024)
ABSTRACT: One branch of IPR that is experiencing very rapid development and is very useful is industrial design. The legal protection given to designers by Law Number 31 of 2000 apparently cannot protect designers. In the first case, the plaintiff, as the owner of a registered industrial design, filed a lawsuit because his industrial design was used without permission and this lawsuit was granted by the District Court. However, in the second case of the plaintiff who had registered his industrial design to be used without permission by the defendant, his lawsuit was rejected by the Commercial Court. The research method used in this research is normative research carried out using a statutory approach and a conceptual approach. The sources of legal materials used are primary, secondary and tertiary legal materials, and the legal material analysis techniques used are qualitative in nature. The results show that: 1) Legal protection for a design will be obtained if it meets the requirements of the industrial design law. The object of industrial design legal protection is industrial designs that are new (novelty) and that have been registered with the Directorate General of Intellectual Property Rights. This means that only industrial designs that are novel can be given legal protection. 2). Liability for violations, such as imitation, use, manufacture, sale, import, export and/or distribution of goods granted industrial design rights. Registered designs can be executed inside or outside the Court. The industrial design right holder or licensee can sue the party who imitates the design, by suing the Commercial Court at the District Court.